Musculoskeletal pain among South African flight Attendants: A cross-sectional study - Narotam, Sonia P; Harerimana, Alexis; Pillay, Julian D (Journal of chiropractic humanities, 2025)
The purpose of this study was to provide details on injuries and musculoskeletal pain among South African flight attendants and to explore their knowledge, perception, and utilization of chiropractic care. The study employed a descriptive, cross-sectional design and used a survey for data collection. A total of 108 participants completed the questionnaire from April to November 2022. Data were analyzed descriptively using frequencies, percentages, and cross-tabulations. Mann- Whitney U tests compared 5-point Likert scale responses regarding chiropractic perceptions between users and non-users. The study found that 58% of flight attendants experienced work-related musculoskeletal pain, mainly in the lower back (84.1%) and shoulders (39.7%). Common causes included long shifts (66.7%) and lifting luggage (44.4%). About 32% sought chiropractic care, which 90% found beneficial for both prevention and maintenance. Chiropractic utilization was higher among participants with musculoskeletal pain (41.3%) compared to those without (19.0%, = .014). Knowledge scores did not differ significantly ( = .369). Positive perceptions ( = .004) and preferences ( < .001) were associated with increased utilization, while limited knowledge ( < .001) and discomfort ( = .046) were linked to decreased utilization. Despite a significant number of flight attendants reporting work-related musculoskeletal pain, their limited knowledge of chiropractic influenced their perception and usage of the service. There is a need for the aviation industry to address musculoskeletal risks and provide adequate chiropractic education and care to flight attendants.